Closing the gap: an urgent need for newborn screening of organic acid disorders in developing countries - Vankwani, Soma; Wasim, Muhammad; Mirza, Munazza Raza; Awan, Fazli Rabbi (Journal of the Pakistan Medical Association, 2024)
Organic acid disorders are rare inherited metabolic disorders of key metabolic pathways. For the identification of specific organic acids, investigation of urinary metabolites and genetic testing are required through newborn screening programmes. Delayed diagnosis leads to complications, such as cardiac attacks, respiratory problems, neuro-developmental disorders, intellectual disability, and even premature death. The burden of such inherited disorders is quite high in developing countries of South Asia due to high rate of consanguinity in the region. Unfortunately, such disorders are left untreated due to the lack of screening facilities in such countries. The current narrative review was planned to highlight the urgent need for closing this gap and implementing effective newborn screening programmes for organic acid disorders in developing countries. ---Continue